2013
DOI: 10.1016/j.msec.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium surface anodization with CaP incorporation on human osteoblastic response

Abstract: In this study we investigated whether anodization with calcium phosphate (CaP) incorporation (Vulcano®) enhances growth factors secretion, osteoblast-specific gene expression, and cell viability, when compared to acid etched surfaces (Porous®) and machined surfaces (Screw®) after 3 and 7 days. Results showed significant cell viability for Porous and Vulcano at day 7, when compared with Screw (p=0.005). At the same time point, significant differences regarding runt-related transcription factor 2 (Runx2), alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…At day 21 in this study there was only modest upregulations of ×1.7 and ×1.4‐fold changes for the cpTi and the CaP‐TiTi surfaces, respectively. Previous studies investigating RUNX2 expression have included an earlier time point, that is, at days 1, 3, or 4 . −38 The inclusion of earlier time points in the present study may have provided a better baseline and more meaningful comparison of fold change analysis for RUNX2.…”
Section: Discussionmentioning
confidence: 95%
“…At day 21 in this study there was only modest upregulations of ×1.7 and ×1.4‐fold changes for the cpTi and the CaP‐TiTi surfaces, respectively. Previous studies investigating RUNX2 expression have included an earlier time point, that is, at days 1, 3, or 4 . −38 The inclusion of earlier time points in the present study may have provided a better baseline and more meaningful comparison of fold change analysis for RUNX2.…”
Section: Discussionmentioning
confidence: 95%
“…More CaP deposition is believed to promote osteoblast cell growth and attachment on titanium [28][29][30] because CaP is necessary component composing osteoblast cells. Therefore the increased osteoblast cell attachment on ECAPed CP-Ti can be understood by this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would appear that only two studies found in the literature specifically analyze BMP-2 production by osteoblasts in vitro , although the use of exogenous BMP-2 in in vitro studies on titanium discs is frequently mentioned in the literature ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%